The role of leadership skills in organizational trust Analytical research center in the Ministry of Higher Education and Scientific Research, Iraq - جادر سهير عادل; مرجاح زهراء غانم (Journal of Economics and Administrative Sciences, 2016)
Formed leadership skills and organizational trust Based on intellectual that underpinned the current research, as represented leadership skills variable interpretative represented in organizational trust-response variable. The research aims to test the relationship and the impact of leadership skills dimensions in organizational trust dimensions for the purpose of achieving its objectives were formulated hypotheses main relate to test the effect and the relationship between the variables of research for the purpose of testing those hypotheses applied research on a sample of heads of departments and officials of the people at the center of the Ministry of Higher Education and Scientific Research, where the sample was composed (90) is responsible (Director of the Department, and an official Division) depending on the resolution as an essential tool for the collection of data and information and in order to test hypotheses and search scheme has been adopted descriptive analytical method in addition to the use of statistical analysis program ((Spss to get to the results. Based on the description of the research variables, diagnosis and testing of hypotheses and search scheme has come to a set of conclusions, including: There is a significant correlation between the variables in terms of leadership skills and confidence in the regulatory Bmngarath ministry researched The existence of a significant effect relationship of leadership skills in terms of the variables in terms of organizational trust variables in the ministry researched Based on the findings of the research findings has developed a set of recommendations, the most important was the need to invest and effect correlation between the research variables in the ministry researched in the future plans of the Ministry for the benefit of its data to improve performance and enhance confidence in the various organizational levels.